T(H)1, T(H)2, and T(H)17 cells instruct monocytes to differentiate into specialized dendritic cell subsets. - Alonso, M; Wong, M; Zhang, A; Winer, D; Suhoski, M; Tolentino, L; Gaitan, J; Davidson, MG; Kung, T; Galel, D; Nadeau, K; Kim, J; et al. (2011)
Monocytes and T helper (T(H)) cells rapidly infiltrate inflamed tissues where monocytes differentiate into inflammatory dendritic cells (DCs) through undefined mechanisms. Our studies indicate that T(H) cells frequently interact with monocytes in inflamed skin and elicit the differentiation of specialized DC subsets characteristic of these lesions. In psoriasis lesions, T(H)1 and T(H)17 cells interact with monocytes and instruct these cells to differentiate into T(H)1- and T(H)17-promoting DCs, respectively. Correspondingly, in acute atopic dermatitis, T(H)2 cells interact with monocytes and elicit the formation of T(H)2-promoting DCs. DC formation requires GM-CSF and cell contact, whereas T(H) subset specific cytokines dictate DC function and the expression of DC subset specific surface molecules. Moreover, the phenotypes of T cell-induced DC subsets are maintained after subsequent stimulation with a panel of TLR agonists, suggesting that T(H)-derived signals outweigh downstream TLR signals in their influence on DC function. These findings indicate that T(H) cells govern the formation and function of specialized DC subsets.